Инновационные разработки кафедры терапевтической стоматологии ЧГМА (LLC "Endo Press", 2020)
The review of authors methods of diagnostics and stomatology diseases treatment which are worked out at the department for the period of 12 years and which are patented as an invention, are given at this article. The department members developments in endodontic sphere are covered in detail.